1967
DOI: 10.1039/c19670001036
|View full text |Cite
|
Sign up to set email alerts
|

A peroxy-radical of chlorine, Cl·O·O

Abstract: Technology and to the Science Research Council for their support of this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1969
1969
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…This “chlorine peroxide” of ref.32 was generated from KClO 4 by irradiating with γ-rays at 195 K; however, the reported value, g 0 = 2.009, was similar to that of the superoxide anion (O 2 ●− ). As a result, we believe the value reported by Eachus et al [ 32 ] is for an oxygen radical (O ● ). On the other hand, g 0 = 2.0043 is close to g 0 = 2.000, the value for a chlorine radical (Cl ● ), rather than g = 2.0114.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…This “chlorine peroxide” of ref.32 was generated from KClO 4 by irradiating with γ-rays at 195 K; however, the reported value, g 0 = 2.009, was similar to that of the superoxide anion (O 2 ●− ). As a result, we believe the value reported by Eachus et al [ 32 ] is for an oxygen radical (O ● ). On the other hand, g 0 = 2.0043 is close to g 0 = 2.000, the value for a chlorine radical (Cl ● ), rather than g = 2.0114.…”
Section: Resultsmentioning
confidence: 71%
“…In the case of Eachus et al [ 32 ], the ESR parameters reported were g x = 1.9983 and α x = 0.53 mT, g y = 2.0017 and α y = 0.72 mT, and g z = 2.0130 and α z = 1.49 mT for “chlorine peroxide, Cl-O-O”. The g 0 value was g 0 = ( g z + g x + g y )/3 = 2.0043 and α 0 = (α z +α x +α y )/3 = 0.913 mT.…”
Section: Resultsmentioning
confidence: 99%
“…During the course of the study, it became apparent that there remained disagreement between different investigators of the low pressure region for the reaction, 2CIO~Cl 2 +0 2 • Porter [6] was the first to report the existence of the ClO radical in a mixture of chlorine and oxygen after flash photolysis by observing intense vibronic bands from 3100 to 2577 A.· Since its discovery, ClO has been observed in the same ultraviolet region by many investigators, [5,[7][8][9][10][11][12][13][14][15] with various methods of production. The electron spin resonance of the radical has been observed both in rigid solution [16] and in the gas phase [17,18]. Infrared study by the method of matrix iso'lation [19] has identified the dimer, Cl 2 0 2 , but not the radical, ClO.…”
Section: Discussionmentioning
confidence: 94%
“…Other indirect evidence has been presented for the existence of CIOO; [20] however, direct evidence of the existence of ClOO has been obtained only recently. Cole [21] detected an electron spin resonance ascribed to ClOO in an irradiated perchlorate single crystal, and another electron spin resonance was tentatively ascribed to it [16]. In a matrix isolation study, Rochkind and Pimentel [19] assigned a pair of infrared absorption bands to ClOO; and a positive identification of ClOO in an argon matrix was made by Arkell and Schwager [22] in an infrared study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation